2020
DOI: 10.1042/bst20191092
|View full text |Cite
|
Sign up to set email alerts
|

Systems approach to rational combination therapy: PARP inhibitors

Abstract: Poly (ADP-ribose) polymerase inhibitors (PARPi) have demonstrated activity across a broad spectrum of molecular backgrounds and tumor types, with the greatest activity observed in patients with aberrations in the homologous recombination DNA damage repair pathway. Despite remarkable responses in a subset of patients, the response is usually modest and transient due to the almost inevitable emergence of resistance. Tumors develop resistance through rapid adaptation to the effects of PARPi as well as by generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…For instance, TC1 cells were defined by high levels of replication stress, which can be functionally associated with high MAPK activity (Sheu et al , 2012; Klotz-Noack et al , 2020). Tumors with high TC1 cell content were strongly positive for PARP, an important therapeutic target (Sun et al , 2020). It is of note that the CMS subtyping system developed for bulk tissue CRC transcriptomes (Guinney et al , 2015) could not distinguish the CRC cell types that we identified here on the single cell level, as most epithelial cancer cells were assigned to CMS1 or CMS2 with the exception of goblet-like cells that can adopt CMS3 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TC1 cells were defined by high levels of replication stress, which can be functionally associated with high MAPK activity (Sheu et al , 2012; Klotz-Noack et al , 2020). Tumors with high TC1 cell content were strongly positive for PARP, an important therapeutic target (Sun et al , 2020). It is of note that the CMS subtyping system developed for bulk tissue CRC transcriptomes (Guinney et al , 2015) could not distinguish the CRC cell types that we identified here on the single cell level, as most epithelial cancer cells were assigned to CMS1 or CMS2 with the exception of goblet-like cells that can adopt CMS3 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the excellent response rates in both arms and the higher rate of hematologic toxicity in the triplet arm, the study group concluded that gemcitabine plus cisplatin is an efficacious regimen in metastatic germ line BRCA or PALB2 mutant PDAC and that the addition of veliparib offered no OR benefit and suggested gemcitabine and cisplatin as the standard therapy in this population. 46 Other trials are exploring the combination of PARP inhibitors with nonplatinum agents. For instance, a phase I trial (NCT03337087) is evaluating irinotecan, liposome, fluorouracil, and leucovorin with rucaparib as second-line therapy in nonselected and BRCA1/2 or PALB2 selected metastatic PDAC.…”
Section: Combined With Chemotherapymentioning
confidence: 99%
“…The results of several studies conducted in ovarian and breast cancer could be extrapolated in the future to help treat metastatic pancreatic cancer patients such as studies evaluating PI3K (NCT01623349, NCT02208375) and VEGFR signaling (NCT02345265), and cell cycle checkpoint protein inhibitors such as WEE1 (NCT02511795). [46][47][48][49] Despite being one of the most common family of oncogenes, RAS genes have been a notoriously fickle and elusive therapeutic target. Importantly, mutations in KRAS are the initial mutational events for most PDACs (95%).…”
Section: Combined With Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations